Campus activities and events-New campus-Arbor day 002
Students of Norseman Elelmentary School in Fresno look on as a young Eucalyptus tree is planted on their campus in an observance of Arbor Day conducted by the Ornamental Horticulture Club at California State University, Fresno. Participants included (left to right) Dr. John Stremple, superintendent of the Fresno Unified School District; Woodsy Owl, conservation mascot; Kevin Sherman of San Jose, president of the CSUF Ornmental Horticulture Club; and sixth grader Rosanna Sasso, student body president st Norseman School. The Ornamental Horticulture Club contributed 80 trees to be planted on the FUSD's elementary and secondary campuses.